The psychological impact of being on a monitoring pathway for localised prostate cancer: A UK‐wide mixed methods study. Issue 7 (10th June 2019) - Matheson, Lauren; Wilding, Sarah; Wagland, Richard; Nayoan, Johana; Rivas, Carol; Downing, Amy; Wright, Penny; Brett, Jo; Kearney, Therese; Cross, William; Glaser, Adam; Gavin, Anna; et al.
Abstract: Objective: To address concerns over the psychological impact of being on a monitoring pathway following prostate cancer (PCa) diagnosis, this study compared the psychological status of men on active surveillance (AS) or watchful waiting (WW) with men on active treatment (AT) and explored psychological adjustment in men on AS/WW. Methods: Cross‐sectional survey of UK men diagnosed with PCa 18 to 42 months previously (n = 16 726, localised disease at diagnosis) and telephone interviews with 24 men on AS/WW. Psychological outcomes were measured using two validated scales (Short Warwick‐Edinburgh Mental Well‐being Scale [SWEMWBS] and Kessler Psychological Distress Scale). Univariable and multivariable analyses compared outcomes between men on AS/WW and AT. Thematic analysis of interviews was undertaken, informed by a previously developed theory of adjustment to cancer. Results: A total of 3986 (23.8%) respondents were on AS/WW. Overall, psychological outcomes were similar or better in men on AS/WW compared with those receiving AT (SWEMWBS: Poor well‐being; 12.3% AS/WW vs 13.9% AT, adjusted OR = 0.86, 95% CI, 0.76‐0.97; K6: severe psychological distress; 4.6% vs 5.4%, adjusted OR = 0.90, 95% CI, 0.74‐1.08). Interviews indicated that most men on AS/WW had adjusted positively. Men with poorer well‐being were less able to accept, reframe positively and normalise their diagnosis, described receiving insufficient information and support, and reported a lack of confidence in their health care professionals. Conclusions: Most men on AS/WW cope well psychologically. Men making treatment decisions should be given this information. Psychological health should be assessed to determine suitability for AS/WW, and at monitoring appointments. A clear action plan and support from health care professionals is important.